(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, we have tried to explain with examples the origin, etymology of medical terms of Uzbek linguistics, some units with a long history, which are now specialized in medicine, have become a term and are actively used in everyday life.